Scientific production of open access articles on hate speech: a scoping review - Farné, Alessandra; Al Najjar Trujillo, Tamer; Parra Valero, Pablo; Cuevas-Cerveró, Aurora (Revista General de Información y Documentación, 2024)
This work presents a study of scientific publications on hate speech with the objective to map the trends in the field. This study follows a scoping review using the PRISMA-ScR methodology. The search was conducted in four databases (Web of Science, Scopus, Social Science Data Base, and Social Science Research Network) using the terms ‘hate speech’ and ‘communication’. The research analysed a sample of 102 open-access scientific journal articles from the period 2016-2021. The analysis focused on production aspects, topics and relevance of the papers for hate speech studies. The study shows a significant increase in production since 2020. However, a low level of depth and specificity is detected when addressing hate speech. Many articles are loosely or barely related to the topic or do not provide specific definitions. There is a prevalence of studies linked to online cases, though not strictly hate speech but rather general topics of cyberbullying or online harassment and an increase in computer-based methodological approaches. Despite a growing scientific production on the subject, the overall quality of most articles does not offer a significant contribution to the understanding, debate, or prevention of hate speech.
Keywords: Hate speech; Scoping review; Journal articles; Scientific databases; Open access; Definitions; Methodological approaches